Multifunctionalization Modulates Hydroxyapatite Surface Interaction with Bisphosphonate: Antiosteoporotic and Antioxidative Stress Materials - Forte, Lucia; Sarda, Stéphanie; Torricelli, Paola; Combes, Christèle; Brouillet, Fabien; Marsan, Olivier; Salamanna, Francesca; Fini, Milena; Boanini, Elisa; Bigi, Adriana (ACS biomaterials science & engineering, 2019)
Multifunctionalized biomaterials with enhanced bone antiresorptive properties were obtained through adsorption of a bisphosphonate, risedronate, on hydroxyapatite (HA) nanocrystals functionalized with zinc ions and polyethylenimine (PEI). Zn incorporation into the HA structure amounts to about 8 atom %, whereas the PEI content of the bifunctionalized material ZnHAPEIBP is about 5.9 wt %. The mechanism of adsorption and release of the bisphosphonate on ZnHAPEI is compared with that on ZnHA: risedronate adsorption isotherm on ZnHA is a Langmuir type, whereas the isotherm of adsorption on ZnHAPEI is better fitted with a Freundlich model and involved a higher amount of adsorbed risedronate. In vitro cell tests were carried out with a coculture model of osteoblasts and osteoclasts using a model simulating oxidative stress and consequent cellular senescence and osteoporosis by the addition of H2O2. The conditions utilized in the coculture model strongly affect osteoblast behavior. The results show that the composite materials allow an increase in osteoblast viability and recover impairment, revealing a novel characteristic of risedronate that is able to counteract the negative effects of oxidative stress when associated with differently functionalized samples. Both PEI and the bisphosphonate reduce osteoclast viability. Moreover, PEI, and even more risedronate, exerts an inhibitory effect on osteoclast activity.